Feminine discourse in Roman comedy on echoes and voices - Dutsch, Dorota M. (Oxford Oxford University Press, 2008)
Dorota M. Dutsch examines the linguistic features of the lines that the Roman playwrights Plautus and Terence attribute to their female characters, and asks whether their construction of a feminine idiom should be considered as evidence of how Roman women actually spoke.
Electronic reproduction.
Keywords: Plautus, Titus Maccius -- Characters -- Women; Terence -- Characters -- Women; Women in literature; Latin drama (Comedy) -- History and criticism